"Better issues to focus on": Transgender Microaggressions as Ethical Violations in Therapy. (August 2020) - Morris, Ezra R.; Lindley, Louis; Galupo, M. Paz
Negative experiences in healthcare settings have been linked to decreased treatment satisfaction and reduction of future help-seeking behaviors among transgender individuals. The present study used gender-identity based microaggressions as a model for understanding the client–therapist relationship. Using a qualitative approach, we investigated instances of microaggressions from mental health providers as experienced by 91 adults who identified as transgender or gender diverse. Participants completed an online survey and described instances of microaggressions directed towards them from mental health providers. Thematic analysis resulted in four therapy-salient themes: Lack of Respect for Client Identity, Lack of Competency, Saliency of Identity, and Gatekeeping. Our discussion of the results focuses on the examination of microaggressions as ethical guideline violations. We discuss methods to improve the practical application of ethical standards to counseling with transgender clients. Implications for practice, training, and future research are also discussed.